PENGARUH KUALITAS LAYANAN DAN PENGALAMAN TERHADAP KEPUASAN SERTA KEPERCAYAAN WISATAWAN (STUDI PADA WISATAWAN YANG BERKUNJUNG PADA OBYEK WISATA TELAGA MENJER DI WONOSOBO) - Wicaksana, Gandhi Satria; Pujiastuti, Eny Endah; Suratna, Suratna (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2019)
The tourism industry is growing rapidly so research in tourism is also growing rapidly. This study aims to examine the tourist behavior intention in the future, especially post visiting the behavior intention. The problem raised is). Does service quality have a significant effect on tourist satisfaction?. 2. Does the tourist experience have a significant effect on tourist satisfaction?. 3. Does service quality have a significant effect on tourist trust?. 4. Do tourist experiences have a significant effect on tourist trust?. Does tourist satisfaction have a significant effect on tourist trust? The research was carried out at tourist sites, namely the lake of the Wonosobo trail. The sample used was Telaga Menjer visitors who first visited Telaga Menjer tourism object. The number of samples is 115 respondents. The method used is systematic random sampling with analysis techniques using path analysis. The results of the study show that there is a significant effect of Service Quality on Tourist Satisfaction, There is a significant influence of Tourist Experience on Tourist Satisfaction, There is a significant effect of Service Quality on Tourist Trust, There is a significant influence of Tourist Experience on Tourist Trust, There is a significant influence Satisfaction Tourists towards Tourist Trust.